2022
DOI: 10.1177/1759720x221105011
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic differences in the pharmacologic management of osteoarthritis: rapid systematic review

Abstract: Background: Racial and ethnic disparities in osteoarthritis (OA) patients’ disease experience may be related to marked differences in the utilization and prescription of pharmacologic treatments. Objectives: The main objective of this rapid systematic review was to evaluate studies that examined race/ethnic differences in the use of pharmacologic treatments for OA. Data sources and methods: A literature search (PubMed and Embase) was ran on 25 February 2022. Studies that evaluated race/ethnic differences in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Differences in pain and function between racial and ethnic groups may be partially explained through disparities in depressive symptoms, income and related socioeconomic factors, and involvement in physically demanding occupations [6]. A rapid systematic review investigating differences in pharmacologic management of OA among racial and ethnic minorities found that nonselective nonsteroidal anti-inflammatory drugs (NSAIDs) were more commonly used among African American compared to White participants with OA [9 ▪ ]. Importantly, the use of nonselective NSAIDs increases risk of some toxicities, including cardiovascular and gastroduodenal toxicity.…”
Section: Understudied Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in pain and function between racial and ethnic groups may be partially explained through disparities in depressive symptoms, income and related socioeconomic factors, and involvement in physically demanding occupations [6]. A rapid systematic review investigating differences in pharmacologic management of OA among racial and ethnic minorities found that nonselective nonsteroidal anti-inflammatory drugs (NSAIDs) were more commonly used among African American compared to White participants with OA [9 ▪ ]. Importantly, the use of nonselective NSAIDs increases risk of some toxicities, including cardiovascular and gastroduodenal toxicity.…”
Section: Understudied Populationsmentioning
confidence: 99%
“…Importantly, the use of nonselective NSAIDs increases risk of some toxicities, including cardiovascular and gastroduodenal toxicity. While more expensive than nonselective NSAIDs, COX-2 selective NSAIDs carry somewhat less risk and therefore may be a better treatment option for OA patients with certain comorbidities [9 ▪ ].…”
Section: Understudied Populationsmentioning
confidence: 99%
“…It is clear that some patients can be considered “responders” to a given treatment while others can be classified as “non-responders” (discussed in [ 84 ]). This is likely true for any number of treatment options and can likely be attributed to human heterogeneity [ 85 ], as well as disease heterogeneity and structural variation in the disease [ 86 ]. Therefore, conservative care should take into account human and disease heterogeneity in an integrated manner and should not remain as a series of “non-effective/effective” interventions that are implemented individually or sequentially until the time for a joint replacement!…”
Section: Implications From Subtyping For Conservative Treatment For K...mentioning
confidence: 99%